Progress in Lowering the Number of Malnutrition Cases in Toddlers in Bone Regency, South Sulawesi - Mulyati, Zhery; Nasir, Sudirman; Thaha, Ridwan Mochtar (International Journal Papier Advance and Scientific Review, 2021)
This study aims to analyze the factors, thus advancement Kab. Bone in lowering malnutrition case in Toddler. This research uses qualitative research with a case study approach. Data were obtained by in-depth interviews and unstructured observations to 22 resource persons consisting of health workers, policy makers (stake holder), community leaders and cadres. Study results shows that all puskesmas carry out the PSG program, moreover the health worker perform the duties with positive attitude and good awareness. Availability of human resources for health care services for malnourished toddlers is 2-4 people, therefore at posyandu helped by 2-5 cadres. As well as support from stakeholder, and good participation from the community. However, there still a lack of knowledge from the community leaders, and cadres about PSG work program. Moreover, there is a shortfall for the availability of health worker in undernourished toddler, also the lack of awareness by some health workers towards teamwork. Inconclusion, the work program, attitude and health worker awareness, human resource availability, stake holder support, and community participation is proven to play a role in progress to reduce the number of cases of malnutrition at Kab. Bone. Stakeholders are expected to make new adaptations or innovations to adjust to the situation during the Covid-19 pandemic, improve the teamwork system, add health workers who serve in undernourished toddlers, and increase more massive and active socialization about the PSG program